Perjanjian Pembiayaan Mobil Bekas Antara Konsumen Dengan Pt.Armada Finance Cabang Padang - Abd Rahmad; Deddy Fernanda (Fakultas Hukum Universitas Tamansiswa Padang, 2026)
Consumer financing agreements are formed based on the principle of freedom of contract, which creates rights and obligations between financing companies as creditors and consumers as debtors. Such agreements are regulated under Article 1313 of the Indonesian Civil Code, which defines an agreement as a legal act whereby one or more persons bind themselves to one or more other persons. In practice, consumer financing agreements are widely applied in credit-based purchases of used motor vehicles, one of which is implemented by PT. Armada Finance Padang Branch, which provides used car financing facilities to the public. This research addresses three main issues: (1) the implementation of used car consumer financing agreements between consumers and PT. Armada Finance Padang Branch; (2) obstacles encountered in the implementation of such agreements; and (3) efforts undertaken to overcome these obstacles. The research method employed is a sociological juridical approach, with data collected through document studies and interviews. The results indicate that the implementation of the consumer financing agreement involves several stages, namely the application process, consumer survey, reporting and preparation of customer profiles, submission of proposals to the credit committee, credit decision-making, contractual binding, delivery of the used vehicle, installment payment period, payment monitoring or collection, and the retrieval of the Vehicle Ownership Certificate (BPKB). The main obstacles faced include delays in installment payments by consumers and unlawful actions by consumers who pledge or sell the financed vehicle to third parties without the consent of the financing company. Efforts to overcome these obstacles are carried out through the application of Collection Management or Account Receivable (A/R) Management, which serves as a systematic process to manage receivables in order to prevent and minimize potential losses arising from delayed consumer payments.